2019
DOI: 10.7150/thno.28671
|View full text |Cite
|
Sign up to set email alerts
|

Direct in vivo application of induced pluripotent stem cells is feasible and can be safe

Abstract: Increasing evidence suggests the consensus that direct in vivo application of induced pluripotent stem cells (iPSCs) is infeasible may not be true.Methods: Teratoma formation and fate were examined in 53 normal and disease conditions involving brain, lung, liver, kidney, islet, skin, hind limb, and arteries.Results: Using classic teratoma generation assays, which require iPSCs to be congregated and confined, all mouse, human, and individualized autologous monkey iPSCs tested formed teratoma, while iPSC-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Single nucleotide polymorphism (SNP) arrays are based on probe binding and can detect changes in a genome with higher resolution (kb) than G-banding (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). This method enables us to study copy number variations (CNVs), >20% mosaicism and loss of heterozygosity (LOH) but on the other hand, it is unable to detect <20% mosaicism, balanced chromosomal translocations, and inversions [30].…”
Section: Single Nucleotide Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphism (SNP) arrays are based on probe binding and can detect changes in a genome with higher resolution (kb) than G-banding (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). This method enables us to study copy number variations (CNVs), >20% mosaicism and loss of heterozygosity (LOH) but on the other hand, it is unable to detect <20% mosaicism, balanced chromosomal translocations, and inversions [30].…”
Section: Single Nucleotide Polymorphismmentioning
confidence: 99%
“…While some discuss the use of undifferentiated hiPSCs as a therapy product [18,19], the majority of hPSCs applications assume their directed differentiation before use, since undifferentiated cells can pose a risk of tumorigenicity. Many different cell types have been generated from hPSCs and some have already been used in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Human iPSCs were generated, cultured, and characterized as we previously described [20]. Briefly, peripheral blood nucleated cells were isolated and infected with Sendai viruses carrying a polycistronic construct of human Klf4, Oct3/4, Sox2, and c-Myc.…”
Section: Generation and Culture Of Human Ipscsmentioning
confidence: 99%
“…Cells were cultured on dishes coated with Matrigel diluted at 60: 1 (BD Biosciences) in mTeSR1 medium (STEMCELL Technologies, Canada). iPSC clones were amplified and then characterized by assessing the expression of pluripotency markers and through in vitro differentiation, alkaline phosphatase activity, and teratoma formation assays, in addition to karyotyping [20].…”
Section: Generation and Culture Of Human Ipscsmentioning
confidence: 99%
“…These cell-sorting technologies maintain the quality of transplanted cells and improve the safety and effectiveness of cell replacement therapy. Multiple animal trials have shown that iPSC transplantation is successful and safe in treating neurological diseases [146][147][148], and human clinical trials of Parkinson's disease using iPSCs are ongoing and observed [149][150][151]. Therefore, the iPSC treatment is expected to become a promising method for PD patients.…”
mentioning
confidence: 99%